HUBUNGAN PENGETAHUAN TENTANG MENSTRUASI DENGAN KESIAPAN DALAM MENGHADAPI MENARCHE PADA SISWI SDN ASRIKATON 1 - Silvia Novitasari; Hartati Eko Wardani; Desi Ariwinanti (Preventia : The Indonesian Journal of Public Health, 2018)
ABSTRACT: Menarche is the first menstruation as a natural process that occurs in the reproductive female. Menstruation is the release of the wall of the uterus (endometrium) accompanied by a reguler and normal bleeding every month from the uterus as a sign that the reproductive organs have matured. Knowledge of menstruation is crucial for female adolescent in facing menarche, so that they are ready to face menarche. Otherwise, the lack of knowledge will lead to erroneous assumptions and behavior, such as assuming that menarche is a disease, and also anxiety. The purpose of this study was to determine the correlation between knowledge of menstruation and the readiness of menarche on female adolescents at SDN Asrikaton 1, Pakis District, Malang Regency. This research used the design of Correlational research with Cross sectional approach. Samples were obtained using the technique of Total sampling the 35 female students (grade IV, V, VI) at SDN Asrikaton 1. Samples studied were female students who had not experienced menarche. Data were collected by using questionnaire, and then statistically analyzed by the methode of Chi-square. Based on the results Statistical analysis showed the significance value (p-value) of 0.000. Therefore, it can be concluded that there was a significant correlation between knowledge of menstruation and the readiness of menarche on female adolescents at SDN Asrikaton 1.Keyword: knowledge, menstruation, menarche, readiness    ABSTRAK: Menarche adalah menstruasi pertama yang merupakan proses alami yang terjadi pada wanita reproduktif. Menstruasi adalah pelepasan dinding rahim (endometrium) disertai perdarahan secara teratur dan normal yang terjadi setiap bulan dari rahim sebagai tanda bahwa organ reproduksi telah matang. Pengetahuan yang baik terkait menstruasi sangat diperlukan siswi dalam menghadapi menarche, agar mereka siap menghadapi menarche. Jika tidak, akan menimbulkan anggapan yang keliru terkait menarche, seperti menganggap bahwa datangnya menarche sebagai suatu penyakit, sehingga menimbulkan kecemasan. Tujuan dari penelitian ini adalah untuk mengetahui hubungan pengetahuan tentang menstruasi  dengan kesiapan dalam menghadapi menarche pada siswi SDN Asrikaton 1 Kecamatan Pakis Kabupaten Malang. Penelitian ini menggunakan desain penelitian korelasional dengan pendekatan cross sectional, menggunakan teknik total sampling pada 35 siswi kelas IV, V, VI SDN Asrikaton 1 yang belum mengalami menarche. Pengumpulan data menggunakan kuesioner dengan analisis data yaitu univariat dan bivariat menggunakan chi square. Berdasarkan hasil penelitian didapatkan nilai p-value 0,000. Hasil ini menunjukkan adanya hubungan yang signifikan antara pengetahuan mengenai menstruasi dengan kesiapan dalam menghadapi menarche pada siswi SDN Asrikaton 1.Kata Kunci: pengetahuan, menstruasi, menarche, kesiapan